2018
DOI: 10.1016/j.drugalcdep.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Gender and race as correlates of high risk sex behaviors among injection drug users at risk for HIV enrolled in the HPTN 037 study

Abstract: Since AA women report high-risk sex behaviors more than other demographic groups, behavioral interventions for HIV risk reduction among PWID may benefit from focusing on sex-risk reduction among AA women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
6
1
Order By: Relevance
“…Several studies have shown that SDU decreases risk perception [ 3 , 28 ] and has been associated with riskier sexual practices [ 29 , 30 , 31 ]. Among the most common risk practices among sexualized drug users are the reduced use of condoms [ 32 , 33 ], multiple casual sexual partners [ 34 , 35 ], and unconventional sexual practices (i.e., bondage and discipline, dominance and submission, and sadism and masochism (BDSM); fisting, barebacking, or serosorting; [ 36 , 37 ]), which could also facilitate the transmission of HIV [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that SDU decreases risk perception [ 3 , 28 ] and has been associated with riskier sexual practices [ 29 , 30 , 31 ]. Among the most common risk practices among sexualized drug users are the reduced use of condoms [ 32 , 33 ], multiple casual sexual partners [ 34 , 35 ], and unconventional sexual practices (i.e., bondage and discipline, dominance and submission, and sadism and masochism (BDSM); fisting, barebacking, or serosorting; [ 36 , 37 ]), which could also facilitate the transmission of HIV [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, differences in mortality by transmission category may also be modified by sex differences. A study determined that compared with male PWID, female PWID were more likely to have high-risk sex 28 , thereby increasing their risk of mortality from sexually transmitted diseases such as hepatitis. A cohort study conducted in Europe found greater sex differences in all-cause mortality among heterosexual people than among PWID (interaction P = 0.043) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the US is experiencing increases in acute hepatitis C virus (HCV) infections related to injection drug use (Zibbell et al, 2018), indicating that PWID are engaging in injection practices that increase risk for HIV transmission. Importantly, PWID face a dual risk for HIV from injection and sexual behaviors (Hill et al, 2018;Kral et al, 2001;Neaigus et al, 2013;Strathdee & Sherman, 2003), including transactional sex (Astemborski, Vlahov, Warren, Solomon, & Nelson, 1994;Jenness et al, 2011;Rondinelli et al, 2009) and forced sex (Williams, Dangerfield, Kral, Wenger, & Bluthenthal, 2018). This may be why there is a higher prevalence of sexually transmitted infections among PWID compared to the general population (Roth et al, 2016), leading to a growing need to prevent infectious disease spread among PWID.…”
Section: Introductionmentioning
confidence: 99%